Preparing for the Speaking Tasks of the TOEFL iBT® Test: An Investigation of the Journeys of Chinese Test Takers. Issue 1 (20th April 2017) - Yu, Guoxing; He, Lianzhen; Rea‐Dickins, Pauline; Kiely, Richard; Lu, Yanbin; Zhang, Jing; Zhang, Yan; Xu, Shasha; Fang, Lin
Abstract: Language test preparation has often been studied within the consequential validity framework in relation to ethics, equity, fairness, and washback of assessment. The use of independent and integrated speaking tasks in the TOEFL iBT ® test represents a significant development and innovation in assessing speaking ability in academic contexts. Integrated tasks that involve synthesizing and summarizing information presented in reading and listening materials have the potential to generate new test preparation strategies. This study investigated the experiences of over 1, 500 Chinese test takers and 23 teachers who were preparing for the TOEFL iBT speaking tasks. It examined the frequency of use of a number of different test preparation activities and materials, reasons, and expectations for taking preparation courses and the features of preparation courses. In addition, we examined the usefulness of test preparation from two perspectives: students' and teachers' perceptions as well as the relationship between test preparation and performance. Data were collected via questionnaires, focus group discussions, interviews with test takers and teachers, and classroom observations. The data showed that (a) test preparation was a hugely complex, multiple‐components construct, and teaching and learning test‐taking strategies compose the most prominent feature of intensive preparation courses; (b) there were significant age‐related differences in students' preparation activities and focuses, although with small effect sizes; (c) there was a high agreement between teachers and students in their views on the usefulness of test preparation activities; and (d) there existed only a weak relationship between test preparation and performance. The only significant predictor of students' test performance was the frequency of their use of the TOEFL Practice Online TPO ® practice tests. The findings of the study can enhance our understanding of the pedagogical practices that characterize test preparation programs and contribute to the ongoing validity argument for the TOEFL iBT Speaking test. The implications of the findings for test publishers, test takers, teachers, and test preparation schools are discussed with reference to the instructional, learning, and affective aspects of the multifaceted construct of test preparation. Abstract : Report Number: ETS RR‐17–19